Fischer-Clifford Matrices and Character Table of the Maximal Subgroup (29:(L3(4)):2 of U6(2):2 - Abraham Love Prins; Ramotjaki Lucky Monaledi (International Journal of Mathematics and Mathematical Sciences)
The automorphism group U6(2):2 of the unitary group U6(2)≅Fi21 has a maximal subgroup G¯ of the form (29:(L3(4)):2 of order 20643840. In this paper, Fischer-Clifford theory is applied to the split extension group G¯ to construct its character table. Also, class fusion from G¯ into the parent group U6(2):2 is determined.